Effect of hydroxypropylmethylcellulose on transition of water status and physicochemical properties of wheat gluten upon frozen storage. (February 2017) - Xuan, Yi-Feng; Zhang, Yuan; Zhao, Yan-Yan; Zheng, Zhi; Jiang, Shao-Tong; Zhong, Xi-Yang
Abstract: The effect of different levels (0.5%, 1%, and 2%) of hydroxypropylmethylcellulose (HPMC) addition on the rheological, thermal, and physicochemical properties of wheat gluten as well as the transition of water status was investigated during frozen storage (0 d, 15 d, 30 d, and 60 d). Apart from the samples with 2% HPMC, a significant decrease in rheological parameters ( G′, and G″ ) was observed with increasing time of frozen storage for all gluten samples. These results were in agreement with the determination of free sulfydryl content, which suggest that disulfide bonds of gluten were ruptured during frozen storage, and HPMC could inhibit the effect of frozen storage via restraining recrystallization. On the other hand, the analyses of differential scanning calorimetry (DSC) showed that as frozen storage time was prolonged, the content of freezable water ( C FW ) increased significantly for both samples with and without HPMC; however, in the same frozen storage time, C FW dropped progressively with the increase in the levels of HPMC addition. The results of Time-Domain NMR (TD-NMR) also revealed that HPMC could retard the transition of water status from the unfreezable to the freezable so as to lower the amount and size of ice crystals. In addition, the micrographs of scanning electron microscopy (SEM) further confirmed that more disordered and weaker microstructures in gluten without HPMC were induced by frozen storage. On the contrary, more integral and uniform microstructures of gluten with 2% HPMC were observed to demonstrate that HPMC could stabilize gluten network. These results in the present study indicated that HPMC could be used in the food industry as an effective cryoprotectant. Graphical abstract: Highlights: Addition with 2% HPMC stabilized the rheological parameters (G′ and G″) of gluten. HPMC lowered water mobility and restricted an increase in freezable water in frozen gluten. HPMC prevented the breakage of inter-/intra-chain -S-S- of gluten proteins. HPMC protected the microstructure and conformation of gluten network.